A comparative study on indoor air quality (IAQ) between centralised and split unit air conditioning systems in a naval ship - Kamaruddin, Amirul Faiz; Zahaba, Maryam; Tamsi, Nur Sarah Fatihah; Anua, Mohd Khusainy; Hassan, Noor Artika; Nordin, Nur Sazwi; Ariffin, Arman (Science & Technology Research Institute for Defence (STRIDE), 2024)
This study determines the compliance of indoor air quality (IAQ) in areas served by different heating ventilation and air conditioning (HVAC) systems in a naval ship, namely centralised and split unit air conditioning systems. A total of nine IAQ parameters, which include physical parameters (temperature, relative humidity (RH) and air movement (AM)), chemical parameters (formaldehyde (CH2O), particulate matters (PM10), total volatile organic compounds (TVOC) and carbon dioxide (CO2)) and biological parameters (total bacterial count (TBC) and total fungal count (TFC) were assessed using calibrated handheld IAQ devices at ten different areas in the ship. The results show that the percentage of compliance is higher in areas served by centralised air conditioning systems as compared to split unit air conditioning systems. The Mann-Whitney test (p-value < 0.05) shows significant difference between the centralised and split unit air conditioning areas for all the IAQ parameters except for temperature. These findings indicate that centralised air conditioning systems, which can introduce fresh air into their served areas contribute to the decrease of concentration of chemical and biological parameters, provided that the units are well maintained.